Correction to: Incidence, clinical features, and outcomes of COVID-19 in Canada: Impact of sex and age - Jacob O'Brien; Kevin Y. Du; Chun Peng (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.